Development and verification of dynamic structural model of wind turbine tower based on the geometrically exact beam theory - Ma, Lu; Yang, Dinghua; Guo, Hao; Shen, Xin; Zhou, Le (Frontiers in Energy Research, 2025)
Introduction: In this paper, a dynamic structural response simulation program TwrDyn for wind turbine tower is developed based on geometrically exact beam theory model, and the program is verified by comparing with numerical simulation and experiment results.Results and discussion: The results show that TwrDyn program can accurately predict the dynamic deformation and load response characteristics of large wind turbine tower under normal and extreme operation conditions, in which the prediction deviations of tower deformation and load response are less than 6.8% and 5.2%, respectively. The program developed in the present study can provide reliable prediction results for tower response characteristics.